Economic Feasibility of Floating Offshore Wind Farms Considering Near Future Wind Resources: Case Study of Iberian Coast and Bay of Biscay - Castro-Santos, Laura; deCastro, Maite; Costoya, Xurxo; Filgueira-Vizoso, Almudena; Lamas-Galdo, Isabel; Ribeiro, Americo; Dias, João M.; Gómez-Gesteira, Moncho (International journal of environmental research and public health, 2021)
Wind energy resources are subject to changes in climate, so the use of wind energy density projections in the near future is essential to determine the viability and profitability of wind farms at particular locations. Thus, a step forward in determining the economic assessment of floating offshore wind farms was taken by considering current and near-future wind energy resources in assessing the main parameters that determine the economic viability (net present value, internal rate of return, and levelized cost of energy) of wind farms. This study was carried out along the Atlantic coast from Brest to Cape St. Vincent. Results show that the future reduction in wind energy density (2%–6%) mainly affects the net present value (NPV) of the farm and has little influence on the levelized cost of energy (LCOE). This study provides a good estimate of the economic viability of OWFs (Offshore Wind Farms) by taking into account how wind resources can vary due to climate change over the lifetime of the farm.